The use of Iramuteq software in the analysis of textual data in a systematic literature review - Batista, Ruhama Ariella Sabião (2023)
Research in the field of Education has used technology to its advantage when it comes to data analysis and categorization, but specifically in systematic literature review, as this article addresses. One of the possibilities is Iramuteq, free software, linked to the statistical software R and its programming language is python. The statistical analyses performed by its algorithms make it possible to recover the context to which the words belong, organize, classify, and perform a series of analyses that can contribute to the researcher's work. In view of this significant contribution, this article aims to discuss the use of the Iramuteq software based on the possibilities observed in the results of a systematic literature review. Thus, we sought to present the use of Iramuteq based on the potential of the following software reports: lexicographic analysis, similarity analysis and descending hierarchical classification. Despite not exhausting the possibilities of the software in this article, we emphasize the relevance of its use to make the process of textual data analysis more agile, concise and coherent. Furthermore, we emphasize the researcher's figure as an essential part for the adequacy of the use of Iramuteq in research, because it is up to him a previous preparation, such as: the knowledge of the possibilities of Iramuteq reports, for an adequate preparation of the text corpus and the knowledge of the study object itself, to use the reports in an adequate and coherent way with the objectives of the research to be performed.